2013
DOI: 10.9734/bjmmr/2013/4005
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Acupoint Stimulation versus Acupressure on Postoperative Nausea and Vomiting after Abdominal Hysterectomy

Abstract: Aims: To compare between the effectiveness of transcutaneous electrical acupoint stimulation versus Acupressure on post-operative nausea and vomiting in women scheduled for abdominal hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Study by El-Bandrawy AM et al 2013 showed a significant decrease in nausea and vomiting in patients treated by acupressure in addition to anti-emetic drug; while PC6 TEAS was more effective than acupressure in alleviating PONV after abdominal hysterectomy[46]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study by El-Bandrawy AM et al 2013 showed a significant decrease in nausea and vomiting in patients treated by acupressure in addition to anti-emetic drug; while PC6 TEAS was more effective than acupressure in alleviating PONV after abdominal hysterectomy[46]. …”
Section: Discussionmentioning
confidence: 99%
“…Study by El-Bandrawy AM et al 2013 showed that time was an important variable, with significant effects of acupressure in the first 6 h[46]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles of this review (26,29) brought in their evaluation method the SF-36, a questionnaire translated and validated in Portuguese, which because it is generic (30) , it is able to evaluate different aspects, such as quality of life, fatigue and pain, through its domains, and this is a useful tool when it comes to a heterogeneous population, as in the case of hysterectomized women, because it is large, it can be applied regardless of age group, disease or treatment group (30) . Transcutaneous electrical stimulation and P6 acupressure proved to be beneficial, with a high degree of recommendation, in reducing postoperative nausea and vomiting (21,23,28) in this review. Molassiotis et al (31) conducted a similar study using a commercial elastic acupressure bracelet (Seaband®) to reduce nausea and vomiting in women with breast cancer undergoing chemotherapy, this bracelet being an elastic band with a plastic button, to perform only acupressure, without the presence of electric current.…”
Section: Discussionmentioning
confidence: 75%
“…Yang et al (27) A 1B 09/out El-Bandrawy; Emara; Ghareeb (28) A 1B 04/out Lauszus et al (29) B 2B -----…”
Section: Degree Of Recommendation Level Of Evidencementioning
confidence: 99%